2012
DOI: 10.1021/ol301851q
|View full text |Cite
|
Sign up to set email alerts
|

Allyloxy and Propargyloxy Group Migration: Role of Remote Group Participation in the Synthesis of 5-C-Nucleosides and Other Sugar Derivatives

Abstract: In 1-deoxy-xylofuranose derivatives possessing a good leaving group at 2-C, participation of allyloxy and propargyloxy substituents at 5-C results in loss of the 2-C substituent and attack of various nucleophiles at 5-C of the oxonium intermediate. Such participation of a benzyloxy or crotyloxy group leads to dioxabicyclo[2.2.1]heptane rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…in some cases. [110][111][112] Our studies of reactions of alkoxy-substituted acetals showed that the presence of an alkoxy group, which is inductively electron-withdrawing, can accelerate acetal hydrolysis if it can approach the developing carbocationic carbon atom (Scheme 54). 113,114 The rate acceleration trends in hydrolysis were also observed for solvolysis of tosylates (Scheme 55).…”
Section: Account Synlettmentioning
confidence: 99%
“…in some cases. [110][111][112] Our studies of reactions of alkoxy-substituted acetals showed that the presence of an alkoxy group, which is inductively electron-withdrawing, can accelerate acetal hydrolysis if it can approach the developing carbocationic carbon atom (Scheme 54). 113,114 The rate acceleration trends in hydrolysis were also observed for solvolysis of tosylates (Scheme 55).…”
Section: Account Synlettmentioning
confidence: 99%